Fertilizer release kinetics incorporated to torrefied banana-crop residues - Faria, Flaviana A. [UNESP]; Faria, Flavio A. [UNESP]; Mattiolli, Lucas [UNESP]; Dias, Diogenes S. [UNESP]; Gomes Neto, Jose A. [UNESP]; Capela, Jorge M. V. [UNESP]; Crespi, Marisa S. [UNESP]; Capela, Marisa V. [UNESP]; Ribeiro, Clovis A. [UNESP] (Springer Nature, 2021)
Banana-crop represents an essential segment in Brazil’s socio-economic structure. However, the residues of banana-crop discarded cause problems of contamination in the crop and environment. Waste reuse technologies for the production of new chemical compounds with high conditioning and nutritional potential of soils are emerging as an efficient and economically viable way in terms of production and market value. From this perspective, the banana-crop residues torrefied, containing incorporated fertilizers, appears as an alternative to the reuse of that biomass in the generation of a slow-release biofertilizer. Biochar was produced from banana-crop pseudostem by torrefaction at 240 °C (BF sample). Urea (N), KCl (K), and diammonium phosphate (P) were added to BF, then pelletized to produce the BF-N, BF-K, and BF-P fertilizers. The relative water sorption kinetics by time was evaluated using an exponential method, with a maximum of 10.5% (w/w) sorption for the BF-N sample and a maximum adsorption time (95%) of 22.25h. The swelling of BF in water was evaluated by TMA, with a maximum ε = 22.4%. TG and DTG curves were used to obtain the proximate analysis, the thermal stability of the samples, and the urea content overtime of the BF-N sample in an aqueous medium and soil. FTIR spectra allowed to evaluate the interactions of N, P, and K with BF during the production of BF-N, BF-P, and BF-K. Two models, exponential (EM) and quotient (QM), were proposed and assessed for release kinetic parameters of N, P, and K from BF, BF-N, BF-P, and BF-K fertilizers in water and two kinds of soils under controlled conditions. The kinetics parameters allowed a discussion on the mechanisms of nutrient release in both water and soil, and the adjustment of the kinetic release model showed the potential for application as slow-release fertilizers.
Keywords: Banana-crop residues; Release Kinetic; Slow-release fertilizers; Thermal characterization; Torrefaction